Receipt for $1500 contributed by Amelia Earhart - Byrd Aviation Associates (Purdue University Libraries, Archives and Special Collections, 1928)
Receipt for $1500 contributed by Amelia Earhart to Byrd Aviation Associates, July 30, 1928. Letter of appreciation from Richard Byrd to Amelia Earhart acknowledging Earhart’s contribution to the Byrd Antarctic Expedition in the amount of $1500, which Earhart had received for endorsing the Lucky Strike brand of cigarettes, July 30, 1928.